If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4a + 4 = 3 Reorder the terms: 3 + 4 + 4a = 3 Combine like terms: 3 + 4 = 7 7 + 4a = 3 Solving 7 + 4a = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4a = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 4a = 3 + -7 4a = 3 + -7 Combine like terms: 3 + -7 = -4 4a = -4 Divide each side by '4'. a = -1 Simplifying a = -1
| 7x-4-2=0 | | (x+20)+x=210-3x | | 5=-5x-2 | | 3x+8y+6= | | 6-(3x-8)=6-4x | | 8-x-3=-x | | -7(n-9)-(5n-4)=-13n | | V-2=0 | | 7w^2-28=0 | | Y=12-15x | | 2x+105+x=18 | | 1m+2m=-1 | | -12+8u=8u-12 | | [x+4]=4 | | 8s^4-72=0 | | 8s^4-72=0 | | 2w-3+5=3w-1 | | 2w-3+5=3w-1 | | 10p=140 | | [2X-36]=14 | | 10p=140 | | [2X-36]=14 | | 4(w-6)=3(w-9) | | Y+1=6(x+1) | | -9(m+3)-5(6m+8)=-40(m+2)-2 | | 30s^2-13s-3=0 | | -2.1(z+.9)=2.1(z+1.6) | | 4x+93+C=180 | | 2(w-3)-(3+8w)=-7w | | 4z^4=-864z | | y+6+7(y+7)= | | 6y+5-4y=4+y-1 |